Lipidomics to analyze the influence of diets with different EPA:DHA ratios in the progression of Metabolic Syndrome using SHROB rats as a model. (15th August 2016) - Dasilva, Gabriel; Pazos, Manuel; García-Egido, Eduardo; Pérez-Jiménez, Jara; Torres, Josep Lluis; Giralt, Montserrat; Nogués, María-Rosa; Medina, Isabel
Highlights: EPA:DHA ratios influence health benefits in an animal model of Metabolic Syndrome. 1:1 & 2:1 EPA:DHA diets show higher anti-inflammatory/antioxidant activity than 1:2. 1:1 & 2:1 EPA:DHA diets display greater effect on markers of CVD and metabolic disease. The lower susceptibility to oxidation of EPA vs DHA may explain some findings. Abstract: The role of specific proportions of ω-3 EPA and DHA, in the modulation of inflammation and oxidative stress markers associated to the progression of Metabolic Syndrome was investigated. Potential inflammatory eicosanoids and docosanoids were discussed together to biomarkers of CVD, obesity, inflammation and oxidative stress in an animal model of metabolic disorders. Results evidenced a noteworthy health effect of 1:1 and 2:1 EPA:DHA proportions over 1:2 EPA:DHA based diets through a down-regulation in the production of strong pro-inflammatory ω-6 eicosanoids, a decrement of biomarkers of oxidative stress, and a modulation of fatty acid desaturase activities and plasma and membrane PUFAs towards greater anti-inflammatory profiles. Outcomes contribute to the general knowledge on the health benefits of marine lipids and their role on the progress of MetS, inflammation and oxidative stress. Results shed light on controversial protective mechanisms of EPA and DHA to better design dietary interventions aimed at reducing MetS.